2019
DOI: 10.2196/jmir.9818
|View full text |Cite
|
Sign up to set email alerts
|

Server-Focused Security Assessment of Mobile Health Apps for Popular Mobile Platforms

Abstract: Background The importance of mobile health (mHealth) apps is growing. Independent of the technologies used, mHealth apps bring more functionality into the hands of users. In the health context, mHealth apps play an important role in providing information and services to patients, offering health care professionals ways to monitor vital parameters or consult patients remotely. The importance of confidentiality in health care and the opaqueness of transport security in apps make the latter an import… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The lack of transparency, inadequate efforts to secure users’ consent, and dominance of companies who use these data for the purposes of marketing, suggests that this practice is not for the benefit of the consumer 10. Furthermore, the presence of trackers for advertising and analytics, uses additional data and processing time and could increase the app’s vulnerability to security breaches 25. In their defence, developers often claim that no “personally identifiable” information is collected or shared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of transparency, inadequate efforts to secure users’ consent, and dominance of companies who use these data for the purposes of marketing, suggests that this practice is not for the benefit of the consumer 10. Furthermore, the presence of trackers for advertising and analytics, uses additional data and processing time and could increase the app’s vulnerability to security breaches 25. In their defence, developers often claim that no “personally identifiable” information is collected or shared.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, the presence of trackers for advertising and analytics, uses additional data and processing time and could increase the app’s vulnerability to security breaches. 25 In their defence, developers often claim that no “personally identifiable” information is collected or shared. However, the network positions of several companies who control the infrastructure in which apps are developed, as well as the data analytics and advertising services, means that users can be easily and uniquely identified, if not by name.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile communication and app use in health care settings has led to concerns regarding patient privacy [ 16 ] and information security [ 17 - 19 ]. Prior to release, an internal security audit and IT review were conducted in 5 business days despite this process typically taking much longer in general.…”
Section: Discussionmentioning
confidence: 99%
“…Inspection of the code Static analysis [54], [62], [65], [67], Dynamic code analysis [62], [65], [67], Vulnerability apps [51] [51], [54], [62], [65], [67] Security transport issues tests System for Semiautomatic Tests of Relevant Transport Security Issues [57], BProxy tool and Testssl script and the Qualys SSL Labs test suite [61], technical assessment of encrypted and unencrypted data transmission [55], analysis of the Bluetooth Low Energy protocol traffic [54] [54], [55], [57], [61], [65] Technical implementation evaluation…”
Section: ) Evaluation Objectives and Artefactsmentioning
confidence: 99%
“…Mixed methods: analysis of the privacy policies [63], compliance with Data Protection regulation requirements [62], server location [61] [2], [62], [63], [65], [82] and the moment in the app lifecycle at which the evaluation should happen (level of evaluation). Similarly to the evaluation frameworks, most of the studies that suggested or applied various security and/or privacy evaluation techniques specified target mHealth stakeholders who could benefit or adopt them.…”
Section: Compliance Data Protection Regulations Compliancementioning
confidence: 99%